A novel homozygous variant of TMEM260 induced cardiac malformation and neurodevelopmental abnormality: case report and literature review - Peng, Mou; Jing, Siyuan; Duan, Sichen; Lu, Guoyan; Zhou, Kaiyu; Hua, Yimin; Wang, Tao; Yue, Peng; Li, Yifei (Frontiers in Medicine, 2023)
Background Congenital heart disease (CHD) represents the most widespread congenital birth defect among neonates worldwide, leading to substantial expenses and contributing significantly to premature death caused by birth defects. Despite the significance of CHD, research on its etiology remains limited and has failed to provide substantial evidence for the molecular basis of the disease. With the advancement of next-generation sequencing (NGS), genetic screening has become increasingly accessible, offering a greater capability for identifying potential genetic variants associated with CHD. Case presentation Exome sequencing and variant analysis of TMEM260 were performed to obtain genetic data, and clinical characteristics were determined. A complex and severe form of CHD, comprising a persistent truncus arteriosus type I, ventricular septal defect, right aortic arch, as well as critical neurodevelopmental delay and neurological dysfunction, was observed in a patient. This proband presented global muscle hypotonia and a significant delay in gross and fine motor development. Cranial computed tomography scanning showed the presence of bilateral apical, occipital, and temporal subdural effusions; slightly wider bilateral lateral ventricles and annular cisterns; and bilateral cerebral hemispheric parenchyma atrophy. Upon genetic analysis of the patient, a novel homozygous mutation was identified in the TMEM260 gene. The mutation, c.1336_1339DEL, was found to be homozygous and resulted in a frameshift mutation, causing a p.L447Vfs*9 amino acid change. This mutation led to the deletion of a TCTC sequence from positions 1336 to 1339 in the TMEM260 gene, changing leucine to valine at amino acid 447 and introducing a stop codon after the ninth amino acid. This structural deletion in the TMEM260 protein resulted in the loss of gene function. Conclusion This case report presents a newly discovered variant site in the TMEM260 gene and reinforces the relationship between TMEM260 molecular function and differentiation of mesoderm and ectoderm. Furthermore, our findings broaden the spectrum of variants in the TMEM260 gene and contribute to advancing the genetic understanding of CHD.